STRATEGI PENGEMBANGAN WISATA DI PESISIR DANAU POSO KECAMATAN PAMONA PUSELEMBA KABUPATEN POSO - Balingki, Arifin (Katalogis, 2015)
This study aims to analyze the internal and external factors and formulate alternative strategies for the development of coastal tourism Lake Poso. This study is categorised as qualitative descriptive study, with direct observation, interviews and documentation. Snow ball sampling technique is applied in order to obtain the key respondents. There were nine people agreed as the key respondents and SWOT is used to analyse the strategic planning.Â SWOT analysis has several phases as follow: (1) identify the key internal and external factors; (2) determining Factor External Strategies (EFAS) and Internal Strategy Factors (IFAS); (3) Determination of weight to the factors of strengths and weaknesses, opportunities and threats; (4) determining the strategy through SWOT matrixÂ The results show that the value of the power factor is 3.8846, and the weakness factor is 3.4954, the opportunity factor is 3.30625 and threats factor is 3.06733. The potential for the development of Lake Poso coastal tourism Lake Poso is located in quadrant I with the strategy SO (Strength and Opportunities). It is optimize the strength to take advantage of opportunities. Meanwhile, the alternative strategies can be offered as follow: building Partnerships and cooperation by utilizing local natural resources eel fish, increasing the main attraction on each undeveloped tourist potential site by adding tourist attractions, and dividing the zone of the development of the coastal tourist area. As a result it is acknowledged that the role of region as developing coastal tourism area.